2007
DOI: 10.1111/j.1475-1313.2007.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Superior short‐wavelength contrast sensitivity in asthenopics during reflexive readjustments of ocular accommodation

Abstract: The purpose of this work was to characterize contrast sensitivity (CS) under short-wavelength illumination in 20 symptom-free subjects and eight asthenopics: all had normal unaided or corrected visual acuity and no sign of oculomotor disease. Threshold CS was assessed using the von Békésy tracking method from a viewing distance of 2.4 m (0.40 D). Three counterbalanced tasks required central fixation of black-and-white square-wave gratings (1, 5, 10, 14 and 17 c/deg) presented through a low-pass filter blue len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…This hypothesis is consistent with previous work that has shown longerwavelength light (red) interferes with reading performance and that relative L-cone sensitivity is negatively correlated with childrenÕs reading skills (Chase et al, 2003. However, Richter and Knez (2007) proposed that asthenopes may drive their accommodative systems harder with shorter wavelengths of light, thus inducing fatigue. Future studies are needed to investigate these conflicting hypotheses.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This hypothesis is consistent with previous work that has shown longerwavelength light (red) interferes with reading performance and that relative L-cone sensitivity is negatively correlated with childrenÕs reading skills (Chase et al, 2003. However, Richter and Knez (2007) proposed that asthenopes may drive their accommodative systems harder with shorter wavelengths of light, thus inducing fatigue. Future studies are needed to investigate these conflicting hypotheses.…”
Section: Discussionsupporting
confidence: 91%
“…, 2003, 2007). However, Richter and Knez (2007) proposed that asthenopes may drive their accommodative systems harder with shorter wavelengths of light, thus inducing fatigue. Future studies are needed to investigate these conflicting hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…), causes not only eye symptoms, but also gives rise to a parallel increase in musculoskeletal load and symptoms in the neck/scapular area [11]. These complaints may either be physiologically interrelated [12], or be a result of a change in posture e.g. triggered by eye-fatigue [13] or non-optimal spectacle correction [7].…”
Section: Biologically Plausible Pathways With Relevance For Work Relamentioning
confidence: 99%
“…Eye accommodation focuses on wavelengths in the middle of the spectrum, with longer (towards red) wavelengths in virtual focus behind the retina and shorter (towards blue) wavelengths in front of the retina. Less eye accommodation is required to focus short wavelengths on the retina 11 . In a study of 94 office workers, blue‐enriched white light (compared with white light) improved subjective alertness, mood, performance, evening fatigue, concentration and eye discomfort 12 .…”
Section: Lightingmentioning
confidence: 99%
“…Less eye accommodation is required to focus short wavelengths on the retina. 11 In a study of 94 office workers, blue-enriched white light (compared with white light) improved subjective alertness, mood, performance, evening fatigue, concentration and eye discomfort. 12 Other studies have also shown an association between increased psychomotor vigilance and reduced sleepiness with exposure to short wavelength light compared with polychromatic light.…”
Section: Introductionmentioning
confidence: 99%